2007
DOI: 10.1590/s1678-91992007000400010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental envenomation with Crotalus durissus terrificus venom in dogs treated with antiophidic serum - part I: clinical evaluation, hematology and myelogram

Abstract: ABSTRACT:The present study aimed at evaluating clinical and laboratory aspects during experimental envenomation by Crotalus durissus terrificus in dogs treated with antiophidic serum. Twenty-one dogs were divided into three groups of seven animals each. Group I received 1mg/kg venom (sc); Group II received 1mg/kg venom (sc), 50mg antiophidic serum (iv), and fluid therapy including 0.9% NaCl solution (iv); and Group III received 1mg/kg venom (sc), 50mg antiophidic serum (iv), and fluid therapy including 0.9% Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
0
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
2
0
0
5
Order By: Relevance
“…The diminution in red blood cells, globular volume and hemoglobin after crotalic experimental envenomation is consistent with the hematological findings from Nogueira et al (2007) and Nogueira & Sakate (2006), who observed the same results in dogs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The diminution in red blood cells, globular volume and hemoglobin after crotalic experimental envenomation is consistent with the hematological findings from Nogueira et al (2007) and Nogueira & Sakate (2006), who observed the same results in dogs.…”
Section: Discussionsupporting
confidence: 90%
“…Dyspnea and lower respiratory and cardiac frequencies were seen, especially in animals from group VS, which are related to the crotalic venom's myotoxic and neurotoxic action. This goes along with findings from Amaral et al (1991), Nogueira & Sakate (2006) and Nogueira et al (2007).…”
Section: Discussionsupporting
confidence: 76%
“…Nogueira et al, (2007) descreveram em cães, o aparecimento de ataxia, sedação leve a moderada, incapacidade em movimentar os membros, incapacidade de levantar a cabeça, adicionalmente, descreveram que o veneno atinge tanto o sistema nervoso central quanto o sistema nervoso periférico.…”
Section: Propriedades Do Veneno Crotálico De Sinais Clínicosunclassified
“…Devido a ação hemolítica do veneno, inicialmente o hemograma costuma apresentar uma discreta leucocitose com neutrofilia, diminuição do número de hemácias, concentração de hemoglobina e da percentagem do hematócrito (NOGUEIRA, 2007;AZEVEDO-MARQUES et al, 1990;BARRAVIERA, 1990). O diagnóstico de IRA pode ser realizado através da elevação progressiva das concentrações séricas de ureia, creatinina e diminuição do débito urinário, com manifestações clínicas como oligúria e anúria.…”
Section: Propriedades Do Veneno Crotálico De Sinais Clínicosunclassified
“…Na América do Sul os gêneros Bothrops e Crotalus são responsáveis pela maioria dos acidentes ofídicos envolvendo seres humanos e animais (Dourado et al 1988, Kouyoumdjian 1990, Sorensen 1990, Barraviera 1991, Ribeiro 1991, Méndez & Riet-Correa 1995, Sgarbi et al 1995, Pinho et al 2000. O gênero Crotalus da família Crotalidae e sua subespécie Crotalus durissus terrificus são a segunda mais importante causa de acidentes no Brasil (Nogueira et al 2007).…”
Section: Introductionunclassified